Konsep Berinfak Dalam Alquran: Studi Penafsiran Makna Kata “Basith” Dalam Surah Al Isra’ Ayat 29 Dalam Perspektif Ibnu Kaṡir - Amy Rejha; Ahmad Zuhri; Yuzaidi Yuzaidi (STIT Sirojul Falah Bogor, 2023)
Infaq is a middle way to overcome the nature of waste and stinginess that exist in humans. Allah commands His servants to spend some of the good fortune he has given as a form of gratitude and concern for others. So from there I took this title to clarify the meaning of the word